CLINICAL CASE OF OBSTETRIC ATYPICAL HEMOLYTIC UREMIC SYNDROME - SVETLANA CH. Kara-Sal; VADIM G. Mozes; KIRA B. Mozes; ELENA V. Rudaeva; IGOR S. Zakharov; SVETLANA I. Yelgina (Фундаментальная и клиническая медицина, 2019)
Here we present a clinical case of atypical hemolytic uremic syndrome (aHUS) associated with delivery. Even in timely diagnosed patients with aHUS, case fatality rate reaches 29%. Currently, aHUS is considered as a thrombotic microangiopathy, along with typical hemolytic uremic syndrome, thrombotic thrombocytopenic purpura, severe preeclampsia, and HELLP syndrome. There is a considerable genetic predisposition to all abovementioned types of thrombotic microangiopathy; however, additional significant stimulation of the complement system is mandatory for aHUS to occur. In children, it can be triggered by respiratory or gastrointestinal infections, while in women it is typically provoked by pregnancy. High mortality of aHUS is due to its rarity and consequent low awareness, non-specific symptoms at its initiation, and rapid development of multiple organ failure including acute kidney injury due to generalized thrombosis in the microvasculature. Successful treatment of aHUS largely depends on the timeliness of diagnosis, specific therapy with eculizumab in combination with a renal replacement therapy, and rapid delivery according to the protocol on severe pre-eclampsia.